El Dr. Luis Roque Gondra : Su influencia en los estudios económicos argentinos - Liliedal, Augusto M. (1961)
Dr. Luis Roque Gondra died in 1947, in the city of Buenos Aires, the principal scene of his long and outstanding activity. An Argentine economist whose mathematical orientation induced him to apply the deductive method, hence his preference for the psychological and mathematical schools. This inclination dominates his lectures on Political Economy in the Faculty of Economic Science at the University of Buenos Aires and reveals itself in his works which may be considered fundamental. He also published several studies on historical and economic subjects and collaborated in specialized journals and newspapers.